The implementation of the G7 and G20 gender equality goals in Germany - Axel Berger; Sören Hilbrich; Gabriele Köhler (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
In recent years, the Group of Seven (G7) and Group of Twenty (G20) have placed increasing emphasis on gender equality. As part of this focus, the member states of both institutions have set out a series of objectives aimed at advancing gender equality. This report examines the degree to which these goals have been implemented in Germany. First, the gender equality goals that both institutions have set out since 2009 are presented and systematised. The report then investigates the current state of progress in Germany and describesmeasures that have already been undertaken to implement the goals.
Keywords: 330